Integrated management systems building technique: inspection and repair of non-structural elements - Ferraz, G. T.; De Brito, J.; De Freitas, V. P.; Silvestre, J. D. (Revista ALCONPAT, 2015)
The international scientific community has devoted a great deal of attention to the vast area of knowledgeof inspection, diagnosis, maintenance and renovation of buildings, which may be used in the developmentof integrated building management systems. In this article, we provide a framework for the evaluationmethods of the pathology of non-structural elements of buildings, based on current methods, presentingsome of the challenges in this area. We present a model to be enforced in the integrated managementsystems of a building, along with some of the challenges of this area. We also introduce a model to beenforced in the integrated management systems of a building, forming a conductor line and a consistentfoundation for a system to be put in place.Keywords: construction pathology; expert system based on performance; evaluation method; buildingmanagement